O CME NO SISTEMA MUNICIPAL DE ENSINO: UM ESTUDO SOBRE A ATUAÇÃO DO CONSELHO MUNICIPAL DE EDUCAÇÃO DE CACHOEIRO DE ITAPEMIRIM-ES - Portinho, Diego Buffolo (2019)
This study integrates the research line School Practice, Teaching, Society and Teacher Training of the Graduate Program in Teaching, Basic Education and Teacher Training of the Federal University of Espírito Santo and aims to discuss the performance of th